2021
DOI: 10.1016/j.jmig.2020.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Non-extirpative Treatments for Uterine Myomas: Measuring Success

Abstract: To analyze outcomes of nonextirpative treatments for uterine myomas compared with myomectomy. Data Sources: A systematic search of the following databases from inception to January 2020 was performed: Ovid Medline, Embase, PubMed, and Cochrane Controlled Register of Trials. Methods of Study Selection: Two authors reviewed titles and abstracts for relevance, and full articles were obtained and evaluated for inclusion. Studies were included if they compared nonextirpative interventions for uterine myomas to myom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…(2019) who reported the mean symptom reduction at 12-months at 59.9% and lesion volume shrinkage at 37.7% [53]. Moreover, MR-HIFU proved to be effective as regards the sexuality of patients with UFs, as the method was associated with similar post-procedure sexual function scores and re-intervention rates compared to myomectomy [30]. In our opinion the results may be assessed as more than promising.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…(2019) who reported the mean symptom reduction at 12-months at 59.9% and lesion volume shrinkage at 37.7% [53]. Moreover, MR-HIFU proved to be effective as regards the sexuality of patients with UFs, as the method was associated with similar post-procedure sexual function scores and re-intervention rates compared to myomectomy [30]. In our opinion the results may be assessed as more than promising.…”
Section: Discussionmentioning
confidence: 84%
“…According to recent analyses, non-surgical methods may lead to positive effects which are similar to those of myomectomy in various aspects. In regards those methodsthe treatment effectiveness of uterine artery embolization (UAE) was confirmed to the largest extent [30]. Some authors suggested that UAE was a safe and effective mini-invasive treatment modality for symptomatic UFs [21,31].…”
Section: Introductionmentioning
confidence: 99%
“…Whenever possible, patients should be made aware of less invasive and uterine-sparing procedures, which may minimize the risk to the patient. These include myomectomy via minimally invasive techniques when appropriate for fibroid removal and improvement of bulk symptoms or other less invasive techniques such as endometrial ablation or radiofrequency volumetric thermal ablation to control bleeding [31,60]. Myomectomy is recommended for patients wishing to preserve fertility; hysteroscopic myomectomy is generally recommended for submucosal fibroids, while laparoscopic or laparotomic myomectomy is advised for intramural and subserosal fibroids [31].…”
Section: Surgical Managementmentioning
confidence: 99%
“…However, the magnitude of this difference in re-intervention rate was very small (4%) and only present in studies with a mean of at least 3 years of follow-up. 62 There is currently only limited or inconsistent scientific evidence that could inform which procedure should be preferred over another to treat symptomatic leiomyomas in patients who desire uterine preservation for future pregnancy. High intensity focused ultrasound (HIFU) for symptomatic leiomyomata has been investigated in recent years offering the advantages of being non-invasive and outpatient procedure.…”
Section: Introductionmentioning
confidence: 99%